Advanced Maternal Age and Pregnancy Outcomes: A Multicountry Assessment. Issue 1 (March 2015) - Laopaiboon, M.; Lumbiganon, P.; Intarut, N.; Mori, R.; Ganchimeg, T.; Vogel, J.P.; Souza, J.P.; Gülmezoglu, A.M.
Abstract : ( BJOG . 2014;121(suppl 1):49–56)